RELATION OF PRO-INFLAMMATORY MARKERS IN MEN AND WOMEN WITH ONE YEAR OUTCOMES AFTER MYOCARDIAL INFARCTION - E. V. Tavlueva; O. L. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. The evaluation of the prominence of subclinical nonspecific inflammation in men and women with ST-elevation myocardial infarction (STEMI) with different one year outcomes.Material and methods. Totally 223 patients with STEMI included — 56 (25,1%) women, 167 (74,9%) men. At 10-14 day of hospitalization we checked inflammation factors: interleukins (IL) — 1а, 6, 8, 10, 12, С-reactive protein, tumor necrosis factor, neopterin. In the assessment of inflammatory reaction severity in men and women each group was assessed in general, and further was spread by the age: <65 y.o. and >65 y.o.Results. In assessment of the combination endpoint it was found that more significantly vascular events developed in women and made up 47% cases, but in men just 33% (р=0,001). Selecting the patients by age-relevant subgroups it was shown that in the age <65 y.o. women had more frequent vascular episodes, than men in this age: 50% (n=20) and 26% (n=89), respectively (р=0,000). In analysis of the IL-12 it is shown than women, comparing to men have this parameter higher in negative as in positive outcome: in positive prognosis 1,4 times higher (р=0,019), and negative prognosis — 1,6 times (р=0,045). In neopterine analysis, depending on combination endpoint it was found than in men with negative outcome the level of neopterin was significantly higher — 17,41 (9,52; 20,90) nmoles/L, than in men with positive outcome — 10,80 (6,53; 10,91) nmoles/L (р=0,000).Conclusion. Negative prognosis in women with STEMI is associated with the increase of IL-12 by 10-14 day, in men — neopterin. Key words: myocardial infarction, pro-inflammatory markers, gender specifics.